(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study was to investigate the effect of physical exercises and yoga asanas combined with physical exercises on anxiety among junior college volleyball players. Sixty volleyball players aged between 16 and 18 years from junior colleges in Visakhapatnam District were randomly selected as subjects. The subjects were divided into three equal groups of twenty each: Physical Exercise Group (PEG), Yogic Practice Combined with Physical Exercise Group (YPCPEG), and Control Group (CG). The experimental groups underwent their respective training programmes for a period of twelve weeks, while the control group did not participate in any special training. Anxiety was selected as the dependent variable. The pre-test mean values of anxiety for PEG, YPCPEG, and CG were 22.051, 20.951, and 21.101 respectively, and the obtained F-ratio of 0.847 was not significant at the 0.05 level of confidence. The post-test mean values were 20.051, 16.701, and 21.101 respectively, with an obtained F-ratio of 19.614, which was significant at the 0.05 level. The adjusted post-test mean values were 19.773, 17.157, and 20.923 respectively, and the obtained F-ratio of 43.484 was also significant. Scheffe’s post hoc test revealed significant mean differences between PEG and CG (1.151), YPCPEG and CG (3.767), and PEG and YPCPEG (2.63), which were higher than the confidence interval value of 1.028. The findings of the study concluded that both physical exercises and yoga asanas combined with physical exercises significantly reduced anxiety among junior college volleyball players. However, the combination of yogic practices with physical exercises was found to be more effective than physical exercises alone in reducing sports competitive anxiety.